ภาวะผูนำพิสัยเต็มของหัวหนาภาควิชากับประสิทธิผลของภาควิชา - คำฝน1 นภัสวรรณ; เจนอักษร นพดล (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2017)
การวิจัยครั้งนี้มีวัตถุประสงคเพื่อทราบ 1) ภาวะผูนำพิสัยเต็มของหัวหนาภาควิชา 2) ประสิทธิผลของภาควิชา 3) ความสัมพันธระหวางภาวะผูนำพิสัยเต็มของหัวหนาภาควิชากับประสิทธิผลของภาควิชา กลุมตัวอยางที่ใชในการวิจัย คือ ภาควิชาในมหาวิทยาลัยเกษตรศาสตร วิทยาเขตกำแพงแสน จำนวน 33 ภาควิชา ภาควิชาละ 6 คน โดยผูใหขอมูล คือ อาจารย และพนักงาน (สายสนับสนุน) จำนวน 198 คน เครื่องมือที่ใชในการวิจัยเปนแบบสอบถามเกี่ยวกับภาวะผูนำพิสัยเต็ม ตามทฤษฎีของแบสและอโวลิโอ (Bass and Avolio) และประสิทธิผลของภาควิชา ตามแนวคิดของฮอย และมิสเกล (Hoy and Miskel) สถิติที่ใชในการวิเคราะหขอมูล คือ การแจกแจงความถี่ (frequency) รอยละ (percentage) คามัชฌิมเลขคณิต (x̄) สวนเบี่ยงเบนมาตรฐาน (S.D.) และสัมประสิทธิ์สหสัมพันธของเพียรสัน (Pearson,s product-moment correlation coefficient) ผลการวิจัยพบวา 1. ภาวะผูนำพิสัยเต็มของหัวหนาภาควิชา โดยภาพรวมและรายดาน อยูในระดับปานกลาง 2. ประสิทธิผลของภาควิชา โดยภาพรวมและรายดาน อยูในระดับ มาก 3. ภาวะผูนำพิสัยเต็มของหัวหนาภาควิชากับประสิทธิผลของภาควิชา มีความสัมพันธกันอยางมีนัยสำคัญทางสถิติที่ ระดับ .01 THE HEAD DEPARTMENT’S FULL RANGE LEADERSHIP AND THE EFFECTIVENESS OF DEPARTMENT The purposes of this research were to find 1) the head of departments’ full range leadership 2) the effectiveness of department 3) relationship between full range of leadership head department and the effectiveness of department. The sample comprised of 33 department, 6 people per each in department. The respondents consisted of instructor and staff, totally 198 respondents. The research instrument was a questionnaire regarding the model of full range of leadership head of department based on Bass and Avolio,s concept and effectiveness of department based on Hoy and Miskel,s concept. The statistical used for the data were frequency, percentage, mean, standard deviation and Pearson,s product moment correlation coefficient. The major findings of the research were as follow: 1. The full range leadership head of department as a whole and as aspect, were at a moderate level. 2. The effectiveness of department as a whole and as revenue department aspect, were at a high level. 3. There was significant relationships between the model of full range of leadership head of department and the effectiveness of department at .01 levels.